“I WISH COCA HAD…” – LEARNER PERCEPTIONS ON HANDS-ON CORPUS USE IN EFL CONTEXT - İtik, Zehra; Gürdal, Hacer Hande Uysal (Fırat University, 2024)
A growing body of research has examined the integration of corpora into foreign language classrooms in the last few decades. A sub-line of research concerning the interaction between the two fields has been student perceptions. Additionally, the growing integration of online learning into curricula, triggered by the COVID-19 pandemic, has aroused a necessity to explore the application of data-driven learning in online learning environments. The current study, therefore, attempted to elicit learner perceptions on learning vocabulary targeted particularly for speaking skill through direct data-driven learning in an online learning context. The data gathered from the participants (N=28) through a questionnaire and a semi-structured interview revealed that the participants found the use of data-driven learning activities in conjunction with the coursebook and oral production tasks helpful to boost their learning. They did not evaluate corpus consultation as a very challenging task to tackle in general. Overall, the study revealed two significant findings: First, it highlighted that collaborative learning might play a significant role in data-driven learning applications. Second, the findings emphasized the necessity for integration of the audio data to the large, publicly available corpora, such as COCA, which could contribute to future research on exploring the efficiency of data-driven learning for speaking skills.

Son yıllarda, derlemin yabancı dil sınıflarında uygulanmasını inceleyen araştırmaların sayısı giderek artmaktadır. İki alan arasındaki etkileşime ilişkin araştırmanın bir alt alanı da öğrencilerin sınıfta derlem kullanımına yönelik algıları olmuştur. Ek olarak, COVID-19 salgınının tetiklediği çevrimiçi öğrenmenin müfredata entegre edilmesi, çevrimiçi öğrenme ortamlarında veriye dayalı öğrenmenin uygulanmasının etkililiğini araştırma ihtiyacını doğurdu. Bu nedenle mevcut çalışma, çevrimiçi öğrenme bağlamında doğrudan veriye dayalı öğrenme yoluyla özellikle İngilizce konuşma becerisini hedefleyen kelime öğrenimine ilişkin öğrenci algılarını ortaya çıkarmayı amaçlamıştır. Katılımcılardan (N=28) bir anket ve yarı yapılandırılmış görüşme yoluyla toplanan veriler, katılımcıların veriye dayalı öğrenme etkinliklerinin, ders kitabı ve üretime dayalı aktivitelerle birlikte kullanımının öğrenmelerini artırmaya yardımcı bulduklarını ortaya çıkardı. Katılımcılar, derlem kullanımı genel olarak üstesinden gelinmesi çok zor bir görev olarak değerlendirmediler. Genel olarak, çalışma iki önemli bulguyu ortaya çıkardı: Birincisi, çalışma, işbirlikçi öğrenmenin veriye dayalı öğrenme uygulamalarında önemli bir rol oynayabileceğini göstermiştir. İkinci olarak bulgular, COCA gibi halka açık geniş bir derlemde sesli verilerin sunulmasının gerekliliğini vurgulamıştır. Çalışmadan elde edilen veriler, konuşma becerileri için veriye dayalı öğrenmenin verimliliğini irdelemeye yönelik gelecekteki araştırmalara katkıda bulunabilir.
Keşke COCA... İngilizce’yi Yabancı Dil Olarak Öğrenen Öğrenicilerin Sınıfta Uygulamalı Derlem Araçlarını Kullanımına Yönelik Algıları
Keywords: English As A Second Language; İkinci Bir Dil Olarak İngilizce; Instructional Technologies; Öğretim Teknolojileri